Post, Mine, Repeat Social Media Data Mining Becomes Ordinary - Kennedy, Helen; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
'Post, Mine, Repeat is a genuinely ground-breaking and original piece of work, in which Helen Kennedy shares a range of important and revealing empirical insights into the practices of data mining. To my knowledge, no-one before has managed to produce such detailed research into data mining. The book shows how data mining fits into commercial monitoring, into organisations, into activism and into public sector services, how these are changing, and exactly what part data mining plays in empowerment and resistance, as well as surveillance and control. It is accessible, yet it tells some complex stories. This really is a tremendous, agenda-setting piece of work.' - Dr David Beer, University of York 'Helen Kennedy has written an enlightening, informative and utterly convincing book. The focus of Post, Mine, Repeat on "ordinary" uses of data mining is a hugely welcome and much-needed contribution to debates about the role of big data in society. I'm so glad that Kennedy's sane, measured, thoughtful, careful, eloquent, ethical voice is there in these debates, for me to cite, recommend and go back to for guidance whenever I get into arguments on the vitally important topics she covers.' - Professor David Hesmondhalgh, University of Leeds 'This is a much-needed study on the importance of data mining to workers in ordinary organisations and more generally in society. What sets this book apart from other academic studies is its empirical focus: through interviews with users, professional data miners and key agents in organisations, Helen Kennedy tackles the larger issues involved in data mining and renders them concrete. The book is clearly focused and persuasively argued, a must-read for anyone who wants to understand what happens next in the world of Big Data.' - Professor José van Dijck, University of Amsterdam In this book, Helen Kennedy argues that as social media data mining becomes more and more ordinary, as we post, mine and repeat, new data relations emerge. These new data relations are characterised by a widespread desire for numbers and the troubling consequences of this desire, by the possibility of doing good with data and resisting data power, by new and old concerns, and by instability and contradiction. Drawing on action research with public sector organisations, interviews with commercial social insights companies and their clients, focus groups with social media users and other research, Kennedy provides a fascinating and detailed account of living with social media data mining inside the organisations that make up the fabric of everyday life. Helen Kennedy is Professor of Digital Society at the University of Sheffield, UK. She has researched and published widely across the field of digital media, from web homepages to data visualisations, from race, class, gender inequality to learning disability and web accessibility, from web design to social media data mining.
1. Social media data mining becomes ordinary -- 2. Why study social media data mining? -- 3. What should concern us about social media data mining? Key debates -- 4. Public sector experiments with social media data mining -- 5. Commercial mediations of social media data -- 6. What happens to mined social media data? -- 7. Fair game? User evaluations of social media data mining -- 8. Doing good with data: alternative practices, elephants in rooms -- 9. New data relations and the desire for numbers.
Keywords: Social media; Communication; Data mining